District Census Handbook, Chikagalur, Part XIII-A, B, Series-9 - Das, B.K. (Karnataka, 1981)
Village and town Directory, Town Directory, Status Growth History and Functional Category of towns, Physical Aspects and Location of towns, Municipal Finance, Civic and other Amenities, Medical, Educational Recreational and Cultural Facilities, trade, Commerce Industry and Banking, Population by Religion and Scheduled Castes/Scheduled Tribes, Village Directory, Primary Census Abstract.
Keywords: Village and town Directory; Village and townwise Primary Census Abstract